CONTROL OF SUBTERRANEAN TERMITE PESTS Coptotermes sp. (Blattodea: Rhinothermitidae) USING COCONUT SHELL LIQUID SMOKE - Patricia Mandagi; Arthur G. Pinaria; Jackson F. Watung; Frangky J. Paat; James B. Kaligis; Sandra E. Pakasi (Jurnal Agroekoteknologi Terapan, 2023)
Subterranean termite Coptotermes sp. is one of the important pests that pose a threat to agriculture. Coconut shell liquid smoke is the result of a pyrolysis distillation process. The content of compounds in liquid smoke includes phenolic compounds, carboxylic acids, and carbonyls. The objective of the study was to determine the effective concentration of coconut shell liquid smoke to control the subterranean termite Coptotermes sp. This study used a completely randomized design (CRD) with 5 treatments, 1 treatment (control), and 4 replications. Subterranean termites used were 300 subterranean termites, each treatment filled with 15 termites (12 workers and 3 soldiers). The research data was calculated to obtain the total mortality percentage of Coptotermes sp. on the last observation. Data were analyzed using Sidik Ragam (ANOVA). If the concentration of the treatment shows a significant effect, then proceed with the 5% LSD (Least Significant Difference) test. Control of the Coptotermes sp. subterranean termite. with coconut shell liquid smoke grade 3 effect on the mortality of Coptotermes sp. subterranean termites. Treatment with a concentration of 1 ml of coconut shell liquid smoke is effective and economical to be used as an organic insecticide among other treatments in controlling Coptotermes sp. subterranean termites. Keywords: Control, Mortality, Rayap Subteran, Coconut Shell Liquid Smoke Abstrak Rayap bawah tanah Coptotermes sp. merupakan salah satu hama penting yang menjadi ancaman dalam bidang pertanian. Asap cair tempurung kelapa merupakan hasil proses destilasi pirolisis. Kandungan senyawa pada asap cair antara lain senyawa fenolik, asam karboksilat dan karbonil. Tujuan penelitian adalah untuk mengetahui konsentrasi asap cair tempurung kelapa yang efektif untuk mengendalikan rayap tanah Coptotermes sp. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan 5 perlakuan, 1 perlakuan (kontrol) dan 4 ulangan. Rayap tanah yang digunakan sebanyak 300 ekor rayap, masing-masing perlakuan diisi 15 ekor rayap (12 pekerja dan 3 prajurit). Data penelitian dihitung untuk memperoleh persentase kematian total Coptotermes sp. pada pengamatan terakhir. Data dianalisis menggunakan Sidik Ragam (ANOVA). Apabila konsentrasi perlakuan menunjukkan pengaruh nyata maka dilanjutkan dengan uji LSD (Beda Nyata Terkecil) 5%. Pengendalian Coptotermes sp. rayap bawah tanah. dengan asap cair tempurung kelapa grade 3 berpengaruh terhadap mortalitas Coptotermes sp. rayap bawah tanah. Perlakuan dengan konsentrasi 1 ml asap cair tempurung kelapa efektif dan ekonomis untuk digunakan sebagai insektisida organik diantara perlakuan lain dalam mengendalikan Coptotermes sp. rayap bawah tanah. Kata Kunci: Pengendalian, Kematian, Rayap Subteran, Asap Cair Batok Kelapa